Computational thermal analysis of FeCrV15+TiB2 coatings on EN48 baseplate by using the COMSOL Multiphysics - Basiru Philip Aramide; Tamba Jamiru; Taoreed Adesola Adegbola; Abimbola Patricia Idowun Popoola; Mathew Olurotimi Adeoti; Rotimi Sadiku; Sisa Pityana (ITEGAM-JETIA)
This study seeks to elucidate the thermal effects of including TiB2 powder on the geometric evolution of FeCrV15 coating using a 3D simulation of the laser cladding process. The process entails applying a coating of FeCrV15 powder onto the EN48 substrate and incorporating TiB2 powder into the coating to evaluate the feasibility of IPG laser-applied coating layers. In order to modify the laser cladding process, the conservation equations of energy, momentum, and mass are linked via the temperature variable and resolved. Intricate hypotheses are employed in mathematical modeling to address the boundary conditions arising from the laser melting of several materials, thereby simplifying issues associated with varying material properties. Moving mesh is employed to ascertain the deformation of a free surface by utilizing the Arbitrary Lagrangian and Eulerian (ALE) methodology. The simulation disregards thermo-capillary forces and their influence on fluid dynamics within the liquefied pool to achieve process optimization. The developed procedure simulation also assesses the thermal dispersion associated with the procedure. The results provide approximate information regarding the influence of TiB2 on the development of clad geometry and the thermal gradient.